2011
DOI: 10.1002/cphc.201000825
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Spatial Constraints and Brønsted Acid Site Locations on para‐Terphenyl Ionization and Charge Transfer in Zeolites

Abstract: The locations of Brønsted acid sites (BAS) in the channels of medium-pore zeolites have a significant effect on the spontaneous ionization of para-terphenyl (PP(3)) insofar as spatial constraints determine the stability of transition states and charge-transfer complexes relevant to charge separation. The ionization rates and ionization yield values demonstrate that a strong synergy exists between the H(+) polarization energy and spatial constraints imposed by the channel topology. Spectroscopic and modeling re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 56 publications
(108 reference statements)
2
36
2
Order By: Relevance
“…Moreover, it might be interesting to compare the present results with the data previously observed with tstilbene 60 for which the reaction mechanism of electron hole pair formation from radical cations was found to be reversed by excitation at the maximum of absorption of the CTC.Consequently, in the present case the excitation of the sample at 532 nm is also expected to induce partial reformation of radical cation. Thus, the presence of a broad band in the 1600-1620 region might also include a contribution of the radical cation reformed upon excitation.This species is indeed expected around 1614 cm -1 according to the resonance Raman experiments reported above.Thus, contrary to what was observed for other parent molecules (biphenyl, p-terphenyl)19,28,39 and other polyaromatics (naphthalene, tetracene)21,29 , the FT Raman spectra allow the observation of the radical cation. This result gives evidence of the high content of radicals stabilized in the zeolite framework and has to be associated with the very slow kinetic of the reaction.…”
contrasting
confidence: 78%
See 3 more Smart Citations
“…Moreover, it might be interesting to compare the present results with the data previously observed with tstilbene 60 for which the reaction mechanism of electron hole pair formation from radical cations was found to be reversed by excitation at the maximum of absorption of the CTC.Consequently, in the present case the excitation of the sample at 532 nm is also expected to induce partial reformation of radical cation. Thus, the presence of a broad band in the 1600-1620 region might also include a contribution of the radical cation reformed upon excitation.This species is indeed expected around 1614 cm -1 according to the resonance Raman experiments reported above.Thus, contrary to what was observed for other parent molecules (biphenyl, p-terphenyl)19,28,39 and other polyaromatics (naphthalene, tetracene)21,29 , the FT Raman spectra allow the observation of the radical cation. This result gives evidence of the high content of radicals stabilized in the zeolite framework and has to be associated with the very slow kinetic of the reaction.…”
contrasting
confidence: 78%
“…Nevertheless, the evolution observed here after mixing p-QPh and H-ZSM-5 is very similar in terms of spectral features and of spectral concentrations to our previous works performed with other polyaromatic molecules in various channel type zeolites. 21,22,23,24,28,29,39,40,41 For all these studies, we have shown that the initial radical cation formed after ionization evolved more or less rapidly toward very long lived charge separated states due to electron transfer from zeolite to the radical cation. Even if the development of the DRUVv bands clearly shows that this second species develops at the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 expense of the radical cation, the assignment has to be done by coupling the UV-visible data with the Raman scattering and EPR experiments (see below) which demonstrate also the formation of two different species all along the time evolution.…”
Section: Eprmentioning
confidence: 96%
See 2 more Smart Citations
“…[7,14] In particular, the remarkable properties of the micropore volume can lead to spontaneous ionization of an electron-donor molecule incorporated in the zeolite and to stabilization of charge-separated states for very long times. [15][16][17] The mechanism of spontaneous charge separation has been well characterized and reported even in the case of polyaromatic molecules with relatively low ionization potential occluded in channel-type zeolites.…”
Section: Introductionmentioning
confidence: 99%